2016
DOI: 10.1159/000446927
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer Patients Have a High Incidence of Severe Periodontitis and Preoperative Dental Care Reduces the Likelihood of Severe Pneumonia after Esophagectomy

Abstract: Background: Poor oral health is a risk factor for causing upper aerodigestive tract tumors, including esophageal cancer. Our aim was to determine the periodontitis rate in our cohort of esophageal cancer patients. We also analyzed whether preoperative dental examination and care reduces the likelihood of severe pneumonia after esophagectomy. Study Design: Between 2003 and 2014, 529 esophageal cancer patients received esophagectomy at Akita University Hospital. We studied 232 patients who had preoperative denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
0
21
0
3
Order By: Relevance
“…The question of whether preoperative oral care by a dentist can decrease postoperative complications remains controversial, because insufficient evidence has been provided in previous studies. In existing studies, which are limited by small sample size or lack of adjustment for confounders, the odds ratios for postoperative pneumonia in patients with oesophageal cancer receiving preoperative oral care from a dentist ranged from 0·21 to 0·37.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question of whether preoperative oral care by a dentist can decrease postoperative complications remains controversial, because insufficient evidence has been provided in previous studies. In existing studies, which are limited by small sample size or lack of adjustment for confounders, the odds ratios for postoperative pneumonia in patients with oesophageal cancer receiving preoperative oral care from a dentist ranged from 0·21 to 0·37.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether preoperative oral care can reduce postoperative pneumonia and mortality. Several studies have suggested that preoperative oral care might be associated with a decrease in postoperative pneumonia after cardiac or cancer surgery, but these were limited by small sample sizes and a small number of participating institutions. The present study used a nationwide database in Japan to examine the association between preoperative oral care by dentists and postoperative pneumonia and all‐cause mortality in patients who underwent cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al [17] mentioned that there were no significant differences in survival between the preoperative chemoradiotherapy and postoperative chemoradiotherapy arm (p > 0.05). However, the postoperative therapy also provides several benefits including decision based on true pathologic stage, more accurate assessment of disease extent to allow for delineation of disease involvement, and less concern about increase in perioperative morbidity and mortality after preoperative induction [4,5,18]. Although CCRT is an important component of therapy, when used alone, it results in unacceptably high rates of relapse and poor long-term survival rates in LN-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another report based on data from 12 European countries and the United States showed that the incidence of anastomotic leakage was 16.5% after minimally invasive esophagectomy 2 . Anastomotic leakage after esophagectomy predisposes the patient to critical conditions, including mediastinitis, pleuritis and acute respiratory distress syndrome (ARDS), and increases the likelihood of reoperation and a longer ICU and hospital stay 1 , 3 . To reduce the incidence of anastomotic leakage, factors to be considered include the anastomotic method (handsewn or stapler), the type of surgical suture used for handsewn anastomosis, the technique used, time required, and blood flow to the esophagus and gastric conduit.…”
Section: Introductionmentioning
confidence: 99%